Implementasi Nilai-Nilai Etika dalam Pembelajaran Bahasa Indonesia untuk Membangun Kemampuan Berpikir Kritis Peserta Didik - Rahmawati Rahmawati; Anggun Citra Dini Dwi Puspitasari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research aims to determine the values of ethics and critical thinking skills in students. This study discusses how implementing ethical values in Indonesian language learning can build critical thinking skills for students. This research employs a literature study that relies on various literature to obtain research data, using a qualitative approach since the data produced is in the form of words or descriptions. The implementation of ethical values in Indonesian language learning is a strategic alternative solution to address the decline of morals in society and the educational environment. Indonesian language learning will enable students to express arguments or opinions using proper and polite Indonesian